Integration Of Islamic Values And Modern Theories In Educational Management - Pujianto; Imroatus Solikhah; Agus Wahyu Triatmo; Rojif Mualim (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
The integration of Islamic values and modern management theories in educational management represents a strategic response to the challenges of contemporary education. Islamic values such as trust (amanah), honesty, justice, responsibility, and deliberation provide strong ethical foundations that can synergize with modern management principles, including efficiency, effectiveness, transformational leadership, Total Quality Management (TQM), and data-driven decision-making. This integration enables the development of an educational management system that not only emphasizes academic excellence, but also prioritizes character formation, moral integrity, and spiritual development. This study employs a qualitative approach through library research, using content analysis of relevant academic literature, scientific journals, books, and policy documents related to Islamic education management and modern management theory. The analysis focuses on synthesizing key management concepts such as POAC (Planning, Organizing, Mobilizing, and Controlling) with core Islamic values to construct a holistic and value-based management framework. The findings indicate that the integration of Islamic values with modern management theories can strengthen institutional governance, enhance leadership effectiveness, and support sustainable quality improvement in educational institutions. This conceptual study contributes to the development of an integrative educational management perspective that balances spirituality, ethics, and modern organizational effectiveness, while providing a theoretical foundation for future empirical research in Islamic education management.